2014
DOI: 10.5755/j01.ms.20.4.6460
|View full text |Cite
|
Sign up to set email alerts
|

Abrasion Properties of Steel Fiber Reinforced Silica Fume Concrete According to Los Angeles and Water Abrasion Tests

Abstract: The current study mainly investigated the influence of different tests on the abrasion resistance of concrete mixed with steel fibers and silica fume. The abrasion resistance was assessed at 28, 56 and 91 days on concretes with water-binder ratios of 0.35 and 0.55 where in some mixes silica fume was substituted by 5 % of cement by weight. Steel fibers of 0.5 % and 1.0 % of concrete volume were also added into the test concrete by replacement of coarse and fine aggregates. The results showed that concrete with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Although the addition of fibers to the mixture affects the flowability, according to El-Dieb and Taha ( 2012), it can be maintained by an optimal fiber-to-cement ratio. Several experiments (Gesoğlu et al 2009;Turk and Karatas 2011;Kang et al 2012;Cheng et al 2014) demonstrated that the abrasion resistance of SCC is increased by a partial replacement of cement with microsilica. Another factor involved is the cyclic freezing and thawing.…”
Section: Production Methods Of Organic Dissipators 21 Required Materi...mentioning
confidence: 99%
“…Although the addition of fibers to the mixture affects the flowability, according to El-Dieb and Taha ( 2012), it can be maintained by an optimal fiber-to-cement ratio. Several experiments (Gesoğlu et al 2009;Turk and Karatas 2011;Kang et al 2012;Cheng et al 2014) demonstrated that the abrasion resistance of SCC is increased by a partial replacement of cement with microsilica. Another factor involved is the cyclic freezing and thawing.…”
Section: Production Methods Of Organic Dissipators 21 Required Materi...mentioning
confidence: 99%
“…Cheng et al found that the compressive strength of concrete increased significantly when only steel fiber was added, but the influence of abrasion resistance was not significant. When silicon powder was added, with the increase of steel fiber and the decrease of water-binder ratio, the compressive strength and abrasion resistance performance were improved; when composite materials were doped with SFRC, the abrasion resistance of cement-based composite increased [20]. Momber studied the abrasion resistant performance of SFRC and found that steel fiber could significantly improve the cavitation resistance of concrete, while steel fiber did not always improve the abrasion resistance of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…A adição de fibras de polipropileno também pode trazer melhorias para a resistência à abrasão do concreto, conforme verificado porHorszczaruk (2009) em um concreto de alta resistência. Já a adição de fibras de aço traz mudanças pouco significativas à resistência à abrasão do concreto, principalmente em misturas com maiores relações água/cimento, sendo observado a delaminação das fibras em alguns casos(CHENG et al, 2014). Silva(2015)O momento negativo é calculado no regime elástico, considerando a não-fissuração do concreto, de acordo com a Equação 14.…”
unclassified